Relationship among hand forces imparted on a viscoelastic hand-handle interface. (October 2019) - Yao, Yumeng; Rakheja, Subhash; Marcotte, Pierre
Highlights: A new sensor is reliable for pressure measurement at a viscoelastic interface. The sensor has low hysteresis and drift, good linearity and repeatability. It can measure interface pressure to estimate contact forces on curved surfaces. Relationships between hand forces are obtained for bare and gloved hand on a handle. Higher grip strength demand was shown for a gloved hand compared to a bare hand. Abstract: Design of a flexible thin-film hand sensor is presented for reliable measurements of the contact pressure/force distribution at a viscoelastic hand-handle interface, including the contact force developed by a gloved-hand grasping a tool handle. The static properties of the developed hand sensor were evaluated in terms of its drift, linearity, repeatability and hysteresis under global as well as local loads. The measured results revealed low hysteresis (<6%) and drift (≈2.9% over 30 s), good linearity (r 2  = 0.99) and repeatability (CoV = 1.5%). Subsequently, an experiment was designed to establish a relationship among the grip, push and contact forces imparted on a flexible hand-handle interface. The hand-handle contact force was measured considering three interface conditions: (i) bare hand grasping an instrumented rigid handle (BH); (ii) hand grasping the instrumented handle covered by an anti-vibration material (MT); and (iii) gloved hand grasping the handle (GV). The measurements with each interface were conducting with five male subjects and nine combinations of grip (10, 30 and 50 N) and push (25, 50 and 75 N) forces. The measured data were analyzed via multiple linear regression method to explore relationships among the grip (Fg ), push (Fp ) and contact (Fc ) forces for each hand-handle interface. The data were further analyzed to investigate the effect of anti-vibration (AV) gloves on the hand grip strength. The relationship obtained for the hand grasping a rigid handle showed good agreement with those in the reported studies, which verified the hand sensor feasibility for application to curved surfaces. The relationship obtained for the bare hand grasping the handle with flexible anti-vibration material, however, showed higher coefficients of grip (αg ) and push (αp ) forces compared to those observed with the rigid handle of the same diameter. A similar trend was also obtained for the gloved hand grasping the handle, which suggested higher grip strength demand for a gloved hand (GV) and hand coupling a viscoelastic handle (MT) compared to the BH condition for realizing the same level of grip/push force combination.